PENGARUH SOCIAL MEDIA MARKETING TERHADAP CUSTOMER ENGAGEMENT DAN LOYALITAS MEREK PADA AKUN INSTAGRAM TOKOPEDIA - Utami, Giska Rizki; Saputri, Marheni Eka (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- The purpose of this study was to determine the effect of social media marketing on brand loyalty through customer engagement on Tokopedia's Instagram.Design/methodology/approach- This research uses quantitative methods and types of causal descriptive research. sample owned by 100 people with a sampling technique using purposive sampling. The data is processed using descriptive analysis and path analysis.Findings- The results of the descriptive analysis of social media marketing variables and brand loyalty are included in the good category, while the customer engagement variable is quite good. The results of path analysis show that social media marketing has a significant effect on customer engagement. The customer engagement has a significant effect on brand loyalty. social media marketing has a significant effect on brand loyalty, and the indirect effect of social media marketing on brand loyalty through customer engagement.Keywords: social media marketing, customer engagement, brand loyalty